Proturans Protura spp. (Entognatha: Protura) - Christopher Tipping (EDIS)
This document provides an overview of Protura, minute soil-inhabiting hexapods characterized by the lack of eyes and antennae, and a 12-segmented abdomen. It details their distribution, morphology, and life history, highlighting their unique development by anamorphosis. Protura are found worldwide in soil, leaf litter, and decaying wood. The article also discusses their collection methods and taxonomic classification, noting that Protura are now considered an order within the class Entognatha. The document emphasizes the need for further research to better understand their ecology and biology. Original publication date July 1998.